2019
DOI: 10.3390/atmos10020094
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Drought Events and Correlations with Large-Scale Ocean–Atmospheric Patterns of Variability: A Case Study in Xinjiang, China

Abstract: This research analyzed the spatiotemporal patterns of drought in Xinjiang (northwestern China) between 1961 and 2015 using the standardized precipitation evapotranspiration index (SPEI). Furthermore, the correlations between Atlantic Multidecadal Oscillation (AMO)/El Niño–Southern Oscillation (ENSO) events and drought were explored. The results suggested an obvious trend toward aggravated drought, with a significant inflection point in 1997, after which the frequency of drought increased sharply. Spatially, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…This was mainly because Xinjiang is located in the westerly-dominated climatic regime, and precipitation is impacted by the latitude wave propagation of the mid-latitude atmospheric circulation and AMO (Huang et al, 2015;Chen et al, 2019). Extreme precipitation in Xinjiang was also correlated with the periodic changes of ENSO and IOD, indicating that although Xinjiang is located inland, climate change in the region is still affected by the Pacific and Indian oceans, which was also reported by Huang et al (2015) and Yao et al (2019). The correlations between the extreme precipitation events (R95p and R99p) and the four climate indices (AMO, ENSO, IOD and NAO) were neither simple linear relationships nor simple positive or negative relationships, but were rather related to an advance or delay in the cycle.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This was mainly because Xinjiang is located in the westerly-dominated climatic regime, and precipitation is impacted by the latitude wave propagation of the mid-latitude atmospheric circulation and AMO (Huang et al, 2015;Chen et al, 2019). Extreme precipitation in Xinjiang was also correlated with the periodic changes of ENSO and IOD, indicating that although Xinjiang is located inland, climate change in the region is still affected by the Pacific and Indian oceans, which was also reported by Huang et al (2015) and Yao et al (2019). The correlations between the extreme precipitation events (R95p and R99p) and the four climate indices (AMO, ENSO, IOD and NAO) were neither simple linear relationships nor simple positive or negative relationships, but were rather related to an advance or delay in the cycle.…”
Section: Discussionmentioning
confidence: 52%
“…Data quality control and the calculation process were conducted in strict accordance with the study requirements. Xinjiang is located in the westerly-dominated climatic regime, and the precipitation is impacted by the latitude wave propagation of the mid-latitude atmospheric circulation and the Atlantic Multidecadal Oscillation (AMO) (Huang et al, 2015;Chen et al, 2019), and the drought variability was closely related to AMO and Multivariate ENSO Index (ENSO3.4) events (Yao et al, 2019), Some studies have shown that changes in AMO can also influence climate change in northwest China (Wu, Zhou & Li, 2016;Dong & Dai, 2015;Meehl et al, 2013). The drought and flood events in Xinjiang had significant correlation with the annual North Atlantic Oscillation (NAO), for periods of less than 10 years (Ling et al, 2017).…”
Section: Data and Selected Indicesmentioning
confidence: 99%
“…They also identified the suitable drought indices for Turkey by comparing the former two EOFs. Several other researches reported that the shapes of EOFs with relative high variance ratios well reflected spatial pattern of drought (Kim et al, 2011;Song et al, 2014;Yao et al, 2019b). However, previous studies analysed drought characteristics either in spatial or temporal scales using single method.…”
Section: Introductionmentioning
confidence: 96%
“…In recent decades, the frequent occurrence of extreme weather events such as heatwaves, cold surges, droughts, floods, and snowstorms has caused considerable casualties and immeasurable economic losses, which have received great attention worldwide [1][2][3][4]. According to the estimation by the relevant departments of the United Nations, weather-related disasters account for 90% of the major global warming has exacerbated the deterioration of the ecological environment, and the extreme weather events have occurred frequently [51,52]. Zhang et al [53] studied the precipitation extremes in Xinjiang from 1957-2009 and found the precipitation extremes exhibiting a wetting tendency after 1980, and this tendency is more obvious in the north than in the south.…”
Section: Introductionmentioning
confidence: 99%